Analisis Kohesi Dan Koherensi Pada Novel Lilin “Terang Itu Membuat Hidupku Gelap” Karya Sanniyah Putri Salsabila Said Serta Implikasinya Dalam Pembelajaran Bahasa Indonesia Kelas VIII SMP Negeri 11 Medan - Ambarita, Anisa Berti Tua; Panggabean, Sarma; Saragih, Elza L.L. (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
This research aims to describe the markers of cohesion and coherence in the novel Lilin "Light That Makes My Life Dark" by Sanniyah Putri Salsabila Said and its implications for Class VIII Language Learning at SMP Negeri 11 Medan. This research use desciptive qualitative approach. Data collection was carried out using library techniques and note-taking techniques. Based on the results of this research, it shows that there are markers of cohesion and coherence in the novel "The Bright Candle Makes My Life Dark by Sanniyah Putri Salsabila Said". First, cohesion is divided into two, namely lexical cohesion and grammatical cohesion. In this study, lexical cohesion was found in 45 data. Of the 45 data, there are 5 synonyms, 13 antonyms, 6 hyponyms, 9 repetitions and 12 collocations. Grammatical cohesion was found in 42 data. From the 42 data, there are 25 pronouns, 3 substitutions, 4 ellipsis and 10 conjunctions. Second, coherence was found in 50 data that described coherence. There are 7 cause-effect relationships, 4 cause-effect relationships, 4 reason-action relationships, 4 background-conclusion, 3 conditions-results, 6 comparisons, 4 applicative, 5 additive, 3 identification, 3 generic-specific, 3 specific-generic , and 4 argumentative. The results of this research provide an important contribution in understanding and applying cohesion and coherence, especially students' writing skills in Indonesian language learning for Class VIII SMP.